Population fluctuation of Anopheles (Diptera: Culicidae) in forest and forest edge habitats in Tucuman Province, Argentina - Dantur Juri, Maria Julia (2010)
The aim of this work was to study the possible effects of forest and forest edge habitats on the population fluctuation of the Anopheles species in northwestern Argentina, taking into consideration the relationship between this fluctuation and climatic variables. This study is one of the first that involves the Anopheles fauna in the country and its dynamics in two different habitats. Sampling was carried out from October, 2002 to October, 2003, in the forest and on the forest edge. Both habitats were compared for species diversity and abundance, and multiple regression analyses were performed to analyze the effects of environmental variables on the population dynamics. Five hundred and sixteen adult specimens of Anopheles species were collected, the most numerous group being Arribalzaga (52.1%), followed by Anopheles (Nyssorhynchus) strodei (20.5%) and Anopheles (Nyssorhynchus) evansae (6.4%). Mosquito abundance was greatest in the forest, the most productive habitat. Samples were collected throughout the sampling period, with a smaller peak in summer. Small numbers of Anopheles (Anopheles) pseudopunctipennis were found throughout the year. Relative humidity, with a 15-day delay, was the factor that most strongly contributed to the temporal sample fluctuation. We conclude that the best season for anopheline development in the study area is from spring to fall, although the period with the greatest transmission risk is the fall, with the greatest An. pseudopunctipennis abundance.